More evidence on the latent benefits of work: bolstered by volunteering while threatened by job insecurity. Issue 3 (3rd May 2020) - Selenko, Eva; Stiglbauer, Barbara; Batinic, Bernad
ABSTRACT: This research examined whether volunteering would grant an alternative route to meaning at work (in the form of the latent benefits of work), even when people are deprived of meaning in times of job insecurity. Two longitudinal studies conducted in Germany (2 waves; n = 110) and the United Kingdom (3 waves; n = 377) showed that volunteering was related to more latent benefits in general, although the specific relationships differed between the countries: In the German sample, volunteering led to more collective purpose and social contacts over time, in the UK sample, it increased time structure and activity. Cross-lagged path analyses further showed that the relationship between volunteering and the latent benefits was reciprocal in both countries: volunteering increased the latent benefits and vice versa. There was limited evidence for the depriving effect of job insecurity, which was found only cross-sectionally. In sum, the results confirm that volunteering can enhance the benefits of work in times of job insecurity and that the effect is reciprocal.